Recovery of salts from ion-exchange regeneration streams by a coupled nanoﬁltration-membrane distillation process - Jiříček, Tomáš; De Schepper, Wim; Lederer, Tomáš; Cauwenberg, Peter; Genné, Inge (Water science and technology, 2015)
Ion-exchange tap water demineralization for process water preparation results in a saline regeneration wastewater (20-100 mS cm(-1)) that is increasingly problematic in view of discharge. A coupled nanofiltration-membrane distillation (NF-MD) process is evaluated for the recovery of water and sodium chloride from this wastewater. NF-MD treatment of mixed regeneration wastewater is compared to NF-MD treatment of separate anion- and cation-regenerate fractions. NF on mixed regeneration wastewater results in a higher flux (30 L m(-2) h(-1) at 7 bar) compared to NF on the separate fractions (6-9 L m(-2) h(-1) at 30 bar). NF permeate recovery is strongly limited by scaling (50% for separate and 60% for mixed, respectively). Physical signs of scaling were found during MD treatment of the NF permeates but did not result in flux decline for mixed regeneration wastewater. Final salt composition is expected to qualify as a road de-icing salt. NF-MD is an economically viable alternative compared to external disposal of wastewater for larger-scale installations (1.4 versus 2.5 euro m(-3) produced demineralized water for a 10 m3 regenerate per day plant). The cost benefits of water re-use and salt recuperation are small when compared to total treatment costs for mixed regenerate wastewater.
Keywords: chlorid sodný; Membranes, Artificial; Distillation; filtrace; Sodium Chloride; destilace; odpadní produkty; čištění vody; Water Purification; Filtration; membrány umělé; Wastewater; Waste Products; Waste Water; odpadní voda